Mitochondria homeostasis: Biology and involvement in hepatic steatosis to NASH - Li Yu-feng; Xie Zhi-fu; Song Qian; Li Jing-ya (Acta Pharmacologica Sinica, 2022)
Mitochondrial biology and behavior are central to the physiology of liver. Multiple mitochondrial quality control mechanisms remodel mitochondrial homeostasis under physiological and pathological conditions. Mitochondrial dysfunction and damage induced by overnutrition lead to oxidative stress, inflammation, liver cell death, and collagen production, which advance hepatic steatosis to nonalcoholic steatohepatitis (NASH). Accumulating evidence suggests that specific interventions that target mitochondrial homeostasis, including energy metabolism, antioxidant effects, and mitochondrial quality control, have emerged as promising strategies for NASH treatment. However, clinical translation of these findings is challenging due to the complex and unclear mechanisms of mitochondrial homeostasis in the pathophysiology of NASH.